Psicopatologia e Psicoanalisi tra conoscenza, diagnosi e cura - 1 Carmela Guerriera, 1 Daniela Cantone (Marp Edizioni, 2019)
The authors propose a psychoanalyticreading of the psychopathology, underlining the shift of the objective, knowledge and care, from the pathology to the subjectthatis the bearer and to the widening, in a horizontal way, to the dimensionIntersubjective, and in a vertical and diachronicway, to that trans generational. The diagnosisisconsidered a necessary and importantobjectiveingoperation, whichallows to reduce the individualcomplexity to constant and generalizablephenomena in an supra-individualdimension, however, support the authors, it must notPrematurelysaturating the cognitive process in itsunfolding in the analyticalrelationship, understood the latteras a place of production of content and unconsciouspsychicforms and notonlyas a scenario of theirmanifestations. Itishighlightedthatpsychoanalyticresearch, in particular in the field of childhood and adolescence, and in relation to severe manifestations of psychicsuffering, hasincreasinglyplacedattention, even for the purpose of diagnosticevaluation, at the levels Primitive and undifferentiatedpsychicfunctioning and the dimensions of pre-mentality in the peri-natal and fetal life. The authors, supported by the mostrecentpsychoanalyticliterature on the topic of psychopathologyaswellas the therapeuticfactors of the cure, alsoexpose some thesis on the evaluation of the new manifestations of the psychicdiscomfort, whichoccurOften by the way of somatic or more genericallyasenigmatic "unbeing" in living assubjects in the world. At the same, the questionistaken on these new clinicalforms, ifthey are evidencedbecause of the changes in the evaluationinstruments or whetherthey are objectivelyidentifiable and classifiable.